Pengaruh Ukuran Perusahaan Dan Profitabilitas Terhadap Return Saham Dengan Likuiditas Sebagai Variabel Moderasi - Vanessa Wahyu Devari; Achmad Badjuri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
Stock Return is the profit obtained by companies, individuals and institutions from the results of the investment policies applied, the factor that influences stock returns is the company's performance. This study aims to find empirical evidence and analyze the effect of firm size and profitability on stock returns with liquidity as a moderating variable is the subject of this study. Companies listed on the Indonesia Stock Exchange (IDX) from 2019-2021 are the subjects of this research. Purposive sampling was used to collect samples from 21 companies. The data used comes from various reliable sources. Company size and profitability are independent variables, stock returns are the dependent variable, and liquidity is a moderating variable. This research collects data using secondary data through documentation techniques. The test results show that firm size has a significant negative effect on stock returns, profitability has a significant negative effect on stock returns, liquidity can weaken the effect of firm size on stock returns, and liquidity can strengthen the effect of profitability on stock returns. Keywords: Company size, profitability, stock return, liquidity